SUSTAINABLE MARITIME POLYTECHNICS: IOT ENVIRONMENTAL MONITORING FOR GREEN CAMPUS ADVANCEMENT - Palapa, Arika; Saifudin, Iksan; Sutopo, Fajar; Kalmareuro, Vennda Uno (Erudio Journal of Educational Innovation, 2026)
This research investigated IoT-based environmental monitoring as green campus infrastructure in maritime education, addressing sustainability imperatives and resource optimization objectives. A comprehensive water quality monitoring system integrating temperature, pH, TDS, and turbidity sensors with cloud analytics was deployed at Politeknik Pelayaran Sulawesi Utara's training pool. Six-month comparative assessment demonstrated substantial environmental improvements including 32% chemical consumption reduction, 22.6% water conservation, and 83% decrease in water quality excursions beyond acceptable parameters. Economic analysis revealed rapid return on investment (3.7 months) with projected five-year cumulative savings of USD 13,333, establishing cost-effectiveness even in resource-constrained contexts. Qualitative assessment through interviews with sustainability experts (n=8), administrators (n=10), and faculty-students (n=12) revealed multidimensional contributions encompassing pollution prevention, institutional credibility enhancement, regulatory compliance documentation, and pedagogical integration potential. Thematic analysis identified resource efficiency and environmental quality as primary benefits, with secondary advantages including sustainability culture development and demonstration effects. The research establishes empirical foundation for scaling automated environmental monitoring across maritime institutions as economically viable green campus infrastructure supporting comprehensive sustainability frameworks and maritime industry environmental transformation alignment.